Precision Farming and Protected Cultivation : Concepts and Applications - Kumar, Sanjeev; Saravaiya, S.N.; Pandey, A. K. (Abingdon, Oxon ; Boca Raton, FL : CRC Press ; Delhi (India) : Narendra Publishing House, 2021)
The book consists of 32 chapters featuring the concepts and applications of precision farmingand protected cultivation broadly covered with theoretical and practical approach. The first 8 chapters areexclusively designed to provide detailed information on concept, need, objectives, benefits, components,applications and limitations of precision farming; laser leveler and its working mechanism, componentsand functioning; mechanized sowing and types of mechanical seeders and their use; approaches formapping of soils and plant attributes; site-specific weed and nutrient management; precision managementof insect-pests and diseases; yield mapping in horticultural crops.An attempt has been made to cover the concept and application of protected cultivation in chaptersfrom 9 to 30 characteristically highlighting the concept of greenhouse technology, its principles as well ashistorical and technological developments, agrivoltaic system, its concept and features, response of plant speciesunder greenhouse conditions, criteria for the selection of crops and varieties for protected cultivation,basic considerations for site selection, orientation and designing of greenhouse structures, climate controlmechanisms for cooling and heating in greenhouses, components, accessories and BIS codes for protectedcultivation, types of Irrigation system for greenhouse production system, growing media for greenhouse cultivation, soil pasteurization namely solarization, steam sterilization, chemical sterilization andaugmentation with biological agents, checking the suitability of soil and water for greenhouse crops, plugtray nursery raising, basics of fertigation in greenhouse production system, packages of practice forgreenhouse cucumber, bell pepper, tomato and melons, potential of pruning as unconventional alternativefor mass multiplication of greenhouse cucumber and tomato, types of soil-less cultures, GAP forprotected cultivation and economic analysis of protected cultivation.Note: T&F does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka.
Greenhouse: Components, Accessories and BIS Codes 17. Irrigation Management in Greenhouse Production System 18. Growing Media for Greenhouse Cultivation 19. Soil Pasteurization 20. Testing Soil and Water Suitability for Greenhouse Crops 21. Plug Tray: A Component of High Tech Nursery 22. Basics of Fertigation in Greenhouse Production System; 23. Production Technology of Cucumber Under Protected Environment 24. Production Technology of Bell Pepper Under Protected Environment 25. Production Technology of Tomato Under Protected Environment 26. Production Technology for Melons Under Protected Environment 27. Pruning: A Virtuous and Unconventional Alternative for Mass Multiplication of Greenhouse Cucumber and Tomato 28. Systems of Soil-less Cultivation 29. Good Agricultural Practices (GAP) for Protected Cultivation 30. Cost Concept and Economic Analysis of Protected Cultivation 31. Understanding The Concept of Vegetable Grafting 32.
OCLC-licensed vendor bibliographic record.
Keywords: Precision farming; TECHNOLOGY / Agriculture / Sustainable Agriculture